Popularna kultura in razredne distinkcije v Sloveniji - Luthar, Breda (Družboslovne razprave, 2012)
The study draws on survey data on the cultural preferences, competencies and practices of a representative sample of the population of the two largest Slovenian cities, Ljubljana and Maribor. The cultural dimensions of class and the role of cultural distinctions in the class structure of both cities are examined. The study focuses on the ways in which non-economic capital, i.e. cultural capital, works in the constitution and reproduction of social inequality The empirical results point to the existence of five separate class-cultural formations or class-specific meaning systems that significantly differ from each another and to a systematic homology between ideal-type cultural classes and four occupational classes (EseC). Tastes are particularly strongly linked to social positions at the bottom and the top of the aesthetic hierarchy. The strongest effect of gender and ethnicity on taste cultures was established at the bottom of the occupational class hierarchy.
Keywords: Množična kultura; Popular culture; Cultural capital; Kulturni kapital; Social classes; Družbeni razredi; Ethnicity; Etničnost; Gender differences; Spolne razlike; Slovenia; Slovenija; sociologija kulture